Survey of Women Physicians' Experience with Elected Leadership Positions - Sasha K. Shillcutt; Sareh Parangi; Sarah Diekman; Reem Ghalib; Robin Schoenthaler; Linda M. Girgis; Ranna Parekh; Hansa Bhargava; Julie K. Silver (Mary Ann Liebert, 2019)
Purpose: Women physicians do not advance in academic promotion or leadership at the same rate as their male counterparts. One factor contributing to academic promotion and advancement is the experience of serving in elected leadership positions. Although >400 women are running for political office in 2018, fewer than a handful are physicians and there has never been a woman physician elected to the Congress. Yet, little is known about women physicians who run for elected positions within their institutions, medical/professional societies, or government. This study sought to examine how women physicians experience elections using a cross-sectional survey of women physicians to gain insight into patterns of reported experiences and perceived barriers to elected leadership positions. Methods: A cross-sectional survey study of 1221 women physicians. Results: 43.8% (N=535) of women physicians ran for an elected office from high school through medical school graduation, in contrast to only 16.7% (N=204) after graduating from medical school. Only 8.5% of women physicians surveyed reported a boss or supervisor encouraged them to run for an elected position. Conclusion: Women physicians are less likely to run for elected positions and for those with previous election experience, the most common barriers cited were lack of institutional time and support, experience, and mentorship.